2009
DOI: 10.1007/s10561-009-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cryopreservation on the pulpal tissue of immature third molars in vitro

Abstract: The purpose of this study was to evaluate in vitro the viability of isolated and non-isolated pulpal tissue of immature third molars after cryopreservation. This study was divided in three different experiments. Experiment 1: Pulpal tissue isolated from 19 third molars was divided in horizontal segments. Each segment was cultured separately in order to evaluate whether differences in growth capacity within the tissue could be found. Experiment 2: Pulpal tissue isolated from 27 third molars was divided in a mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Temmerman et al. (5) proved that cryopreservation of human pulp tissue would be possible if the cryoprotective agent could reach the entire pulp. Consequently, if a novel cryopreservation modality could be invented, as demonstrated by Lee et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temmerman et al. (5) proved that cryopreservation of human pulp tissue would be possible if the cryoprotective agent could reach the entire pulp. Consequently, if a novel cryopreservation modality could be invented, as demonstrated by Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the English-language literature, to our knowledge, previous research into the cryopreservation of hDPSCs has chiefly focused on healthy permanent third molars and premolars (3)(4)(5)(6)(7). To our knowledge, there is a lack of detailed data focusing on the exploration of hDPSCs from the other types of tooth, Cryopreserved hDPSC from diseased vital teeth particularly for diseased but vital teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested different cryopreservation times, which vary from one day to longer periods 11,12 . The time used in the current article for our experiments corresponds to what we found in the literature, as several authors evaluated the cryopreservation effect after 30 days 9,13,14 without observing significant differences in proliferation and differentiation capacity between cryopreserved cells and non-cryopreserved cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of teeth or dental tissues cryopreservation, minimal processing may needed for banking. There are some evidences which are demonstrated the successful cryopreservation of healthy and diseased teeth as well as dental tissues [72][73][74][75][76][77][78]. On the other hand, cryopreservation of DSCs still has been considered as an active area of the researches.…”
Section: Dscs Cryopreservationmentioning
confidence: 99%